A Multistate Outbreak of Human Salmonella Agona Infections Associated With Consumption of Fresh, Whole Papayas Imported From Mexico—United States, 2011. (19th February 2018) - Mba-Jonas, Adamma; Culpepper, Wright; Hill, Thomas; Cantu, Venessa; Loera, Julie; Borders, Julie; Saathoff-Huber, Lori; Nsubuga, Johnson; Zambrana, Ingrid; Dalton, Shannon; Williams, Ian; Neil, Karen P
Abstract : A multistate outbreak of Salmonella Agona was investigated in 2011. Through the combined use of interviews to identify suspect food vehicles, traceback, and novel techniques for analyzing distribution records, papayas from Mexico were identified as the source of the outbreak. Abstract: Background: Nontyphoidal Salmonella causes 1 million food-borne infections annually in the United States. We began investigating a multistate outbreak of Salmonella serotype Agona infections in April 2011. Methods: A case was defined as infection with the outbreak strain of Salmonella Agona occurring between 1 January and 25 August 2011. We developed hypotheses through iterative interviews. Product distribution analyses and traceback investigations were conducted. The Food and Drug Administration (FDA) tested papayas from Mexico for Salmonella. Results: We identified 106 case patients from 25 states. Their median age was 21 years (range, 1–91). Thirty-nine of 61 case patients (64%) reported Hispanic/Latino ethnicity; 11 of 65 (17%) travelled to Mexico before illness. Thirty-two of 56 case patients (57%) reported papaya consumption. Distribution analyses revealed that three firms, including Distributor A, distributed papaya to geographic areas that aligned with both the location and timing of illnesses. Traceback of papayas purchased by ill persons in four states identified Distributor A as the common supplier. FDA testing isolated the outbreak strain from a papaya sample collected at distributor A and from another sample collected at the US-Mexico border, destined for distributor A. FDA isolated Salmonella species from 62 of 388 papaya import samples (16%). The investigation led to a recall of fresh, whole papayas from Distributor A and an FDA import alert for all papayas from Mexico. Conclusions: This is the first reported Salmonella outbreak in the United States linked to fresh, whole papayas. The outbreak highlights important issues regarding the safety of imported produce.